Advances in Research on Epichloë endophytes in Chinese Native Grasses - Song, Hui; Nan, Zhibiao; Song, Qiuyan; Xia, Chao; Li, Xiuzhang; Yao, Xiang; Xu, Wenbo; Kuang, Yu; Tian, Pei; Zhang, Qingping (Frontiers in Microbiology, 2016)
Epichloë fungal endophytes are broadly found in cool-season grasses. The symbiosis between these grasses and Epichloë may improve the abiotic and biotic resistance of the grass plant, but some Epichloë species produce alkaloids that are toxic for livestock. Therefore, it is important to understand the characteristics of the grass-Epichloë s symbiosis so that the beneficial aspects can be preserved and the toxic effects to livestock can be avoided. Since the 1990s, Chinese researchers have conducted a series of studies on grass-Epichloë symbiosis. In this review, we describe the current state of Epichloë endophyte research in Chinese native grasses. We found that more than 77 species of native grasses in China are associated with Epichloë endophytes. In addition, we review the effects of various Epichloë species on native grass responses to abiotic and biotic stress, phylogeny, and alkaloid production. We provide an overview of the study of Epichloë species on native grasses in China and directions for future research.